The supersolid phase of matter - Modugno, Giovanni (Il Colle di Galileo, 2021)
The supersolid is a phase of matter intermediate between a crystal and a superfluid. It was predicted more than fifty years ago, long sought in solid helium and only recently discovered in a quantum gas of magnetic atoms. This article explains how we came to discover the supersolid, how some surprising properties have already been characterized and which others have still to be unveiled.